In vivo Toxicity, Pharmacokinetic Features and Tissue Distribution of N-[2-(2,5-Dimethoxyphenylethyl)]-N’-[2-(5-bromopyridyl)]-thiourea (HI-236), a Potent Non-nucleoside Inhibitor of HIV-1 Reverse Transcriptase - Chen, Chun-Lin; Venkatachalam, Taraco K.; Waurzyniak, Barbara; Chelstrom, Lisa; Uckun, Fatih M. (Arzneimittelforschung, 2001)
N-[2-(2,5-Dimethoxyphenylethyl)]-N’-[2-(5-bromopyridyl)]-thiourea (HI-236, CAS 233271-65-3) possesses potent anti-viral activity against zidovudine-sensitive as well as multidrug-resistant HIV-1 (human immunodeficiency virus) strains. The purpose of the present study was to examine in vivo toxicity, pharmacokinetic features and tissue distribution of HI-236 in mice. HI-236 had an elimination half-life of 85.8 min after i.v. administration and 86.6 min after i.p. administration. The systemic clearance of HI-236 was 4337 ml/h/kg after i.v. administration and 10130 ml/h/kg after i.p. administration. Following i.v. injection, HI-236 rapidly distributed to and accumulated in multiple tissues with particularly high accumulation in lung, adipose tissue, skin, urinary bladder, adrenal gland and uterus + ovary. The concentration of HI-236 in brain tissue was comparable to that in the plasma, indicating that HI-236 easily crosses the blood-brain barrier. Following i.p. injection, HI-236 was rapidly absorbed with a tmax values of 5.6 min and showed linear pharmacokinetics within the dose range of 10–80 mg/kg.Following oral administration, HI-236 was absorbed with a tmax of 5.8 min. The intraperitoneal bioavailability was estimated at 42.9 %, while the oral bioavailability was only 2.2 %. The pharmacokinetic study described herein provides the basis for advanced pharmacodynamic study of HI-236.
Keywords: CAS 233271-65-3; N-[2-(2,5-Dimethoxyphenyl-ethyl)]-N’- [2- (5-bromopyridin-yl)]-thiourea; HI-236, in vivo toxicity, mouse, pharmacokinetics; HIV-1 reverse transcriptase, non-nucleoside inhibitor